Evaluation of Opinions of Individuals in the Late Adulthood Period on the Digital World - Ayhan, Seçil Besim; Başarı, Şengül; Köprülü, Fatma (Cadernos de Educação Tecnologia e Sociedade, 2024)
For successful aging, determining the vital needs and educational needs of individuals in advanced adulthood, and creating training programs to meet these needs is important for the continuity of the socialization process and the socialization of late adult individuals in this process. When the current conditions (pandemic process) are taken into consideration, one of the most important tools of this socialization process is the elements of the digital world. This study aims to reveal the current situation regarding the connections of individuals in late adulthood with the digital world, to determine their needs based on the evaluation of this situation, and to put forward recommendations for meeting these needs. The study was carried out with a qualitative method and is in the case study pattern. The study group consists of 17 late adult individuals over 65. Data were collected through a semi-structured interview form. Descriptive analysis was used in the analysis of the data. As a result of the study, it was revealed that the individuals in the study group used smartphones most frequently, and they followed "Facebook" and "WhatsApp" among the applications. Among the reasons for using social media, following the news and communicating with acquaintances were frequently emphasized. These reasons are also stated as the advantages of the digital world. At the end of the study, recommendations on the usage of technology can be made including information in the form of public service ads and short videos through television channels and sharing application steps visually.